Neutralizing antibody titers against dengue virus correlate with protection from symptomatic infection in a longitudinal cohort - Katzelnick, Leah C. (Proc Natl Acad Sci U S A, 2016)
The four dengue virus serotypes (DENV1–4) are mosquito-borne flaviviruses that infect ∼390 million people annually; up to 100 million infections are symptomatic, and 500,000 cases progress to severe disease. Exposure to a heterologous DENV serotype, the specific infecting DENV strains, and the interval of time between infections, as well as age, ethnicity, genetic polymorphisms, and comorbidities of the host, are all risk factors for severe dengue. In contrast, neutralizing antibodies (NAbs) are thought to provide long-lived protection against symptomatic infection and severe dengue. The objective of dengue vaccines is to provide balanced protection against all DENV serotypes simultaneously. However, the association between homotypic and heterotypic NAb titers and protection against symptomatic infection remains poorly understood. Here, we demonstrate that the titer of preinfection cross-reactive NAbs correlates with reduced likelihood of symptomatic secondary infection in a longitudinal pediatric dengue cohort in Nicaragua. The protective effect of NAb titers on infection outcome remained significant when controlled for age, number of years between infections, and epidemic force, as well as with relaxed or more stringent criteria for defining inapparent DENV infections. Further, individuals with higher NAb titers immediately after primary infection had delayed symptomatic infections compared with those with lower titers. However, overall NAb titers increased modestly in magnitude and remained serotype cross-reactive in the years between infections, possibly due to reexposure. These findings establish that anti-DENV NAb titers correlate with reduced probability of symptomatic DENV infection and provide insights into longitudinal characteristics of antibody-mediated immunity to DENV in an endemic setting.